The coordinate-based meta-analysis of neuroimaging data - Samartsidis, P; Montagna, S; Johnson, T; Nichols, T (Institute of Mathematical Statistics, 2017)
Neuroimaging meta-analysis is an area of growing interest in statistics. The special characteristics of neuroimaging data render classical meta-analysis methods inapplicable and therefore new methods have been developed. We review existing methodologies, explaining the benefits and drawbacks of each. A demonstration on a real dataset of emotion studies is included. We discuss some still-open problems in the field to highlight the need for future research.